2021
DOI: 10.1177/2333794x211018350
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Neonatal Outcome are More Common among Babies Born by Cesarean Section than Naturally Born Babies at Public Hospitals in Eastern Ethiopia: A Comparative Prospective Follow-Up Study at Eastern Ethiopia

Abstract: The adverse neonatal outcome is defined as the presence of birth asphyxia, respiratory distress, birth trauma, hypothermia, meconium aspiration syndrome, neonatal intensive care admission, and neonatal death. It is a major concern in developing countries, including Ethiopia. This study tried to identify predictors of adverse neonatal outcomes at selected public hospitals in Eastern Ethiopia. A hospital-based prospective follow-up study was conducted in three public hospitals in Eastern Ethiopia from June to Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…A study by Sowemimo et al 13 showed that out of 66 deliveries conducted instrumentally, 45.5% resulted in admission to NICU, also, the risk of adverse neonatal outcome was increased in mothers who had cesarean section. 30 Undoubtedly, there could exist some confounding factors beyond the scope of the current study.…”
Section: Discussionmentioning
confidence: 94%
“…A study by Sowemimo et al 13 showed that out of 66 deliveries conducted instrumentally, 45.5% resulted in admission to NICU, also, the risk of adverse neonatal outcome was increased in mothers who had cesarean section. 30 Undoubtedly, there could exist some confounding factors beyond the scope of the current study.…”
Section: Discussionmentioning
confidence: 94%
“…This result is in line with a similar study conducted in the Northern part of Ghana [ 33 ]. Moreover, previous studies have consistently reported a significant association between caesarean delivery and an increased likelihood of NICU admission among neonates [ 34 36 ]. Indeed, babies referred to the neonatal intensive care unit (NICU) are more likely to have been delivered by caesarean section.…”
Section: Discussionmentioning
confidence: 99%